2009
DOI: 10.4103/0253-7613.58510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clonidine on blood glucose levels in euglycemic and alloxan-induced diabetic rats and its interaction with glibenclamide

Abstract: Objectives:Clonidine, a known antihypertensive, is currently used for many purposes including diabetic gastroparesis, postmenopausal hot flushes, opioid/nicotine/alcohol withdrawal. Its effects on carbohydrate metabolism appear to be variable. Hence, the present study was undertaken to evaluate the influence of clonidine on euglycemic and alloxan -induced diabetic rats and its interaction with glibenclamide.Materials and Methods:Alloxan - induced (150 mg/kg, i.p) diabetic rats were divided into six groups of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…To induce diabetes gastroparesis, overnight fasted rats were received a single intraperitoneally injection of alloxan monohydrate at 175 mg/kg. 9,[13][14] After 72 h, blood glucose was checked by glucometer (Elegance, Frankenberg, Germany). Rat with fasting blood glucose higher than 250 mg/dL was considered as diabetic.…”
Section: Induction Of Gastroparesismentioning
confidence: 99%
“…To induce diabetes gastroparesis, overnight fasted rats were received a single intraperitoneally injection of alloxan monohydrate at 175 mg/kg. 9,[13][14] After 72 h, blood glucose was checked by glucometer (Elegance, Frankenberg, Germany). Rat with fasting blood glucose higher than 250 mg/dL was considered as diabetic.…”
Section: Induction Of Gastroparesismentioning
confidence: 99%
“…Manjunath et al in their study carried on alloxan induced diabetic rats have concluded that clonidine has hyperglycemic effects and also interact with glibenclamide to reduce its hypoglycemic activity. 1 Clonidine is α2 receptor agonist and these authors have proposed that this hyperglycemia could be due to inhibition of insulin release, stimulation of growth hormone release and due to increased hepatic glycogenolysis by clonidine. In this study, we also found that tamsulosin interact with glibenclamide to reduce its hypoglycemic activity, however tamsulosin did not cause hyperglycemia in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with many co-morbid conditions such as hypertension, obesity, cardiovascular disorder, dyslipidemia, mostly due to hyperglycemia caused by insulin deficiency or resistance to insulin. 1 In elderly male patients suffering from diabetes mellitus (DM), benign prostatic hyperplasia (BPH) is often associated for which α receptor antagonist such as prazosin, doxazosin, and selective α1A antagonist such as tamsulosin are frequently used. 2 Obesity, elevated blood glucose level and diabetes have been mentioned as risk factors for benign prostatic hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…17 The study was done in two phases. 12,13,16,18 In phase I, Oral Glucose Tolerance Test (OGTT) was done with 3 different doses of the methanolic extract of Acorus calamus (100, 150 and 200mg/kg).…”
Section: Instrumentmentioning
confidence: 99%
“…Only those rats which developed FBS >250mg/dl after 7 days of alloxan administration were taken for study. 6,11,15,17,19 Rats were grouped as follows (Table 5). …”
Section: Instrumentmentioning
confidence: 99%